Pharmacological modulation of the voltage-gated neuronal Kv7/KCNQ/M-channel alters the intrinsic excitability and synaptic responses of pyramidal neurons in rat prefrontal cortex slices - Peng, Hui; Bian, Xi-ling; Ma, Fu-cui; Wang, Ke-Wei (Acta pharmacologica Sinica, 2017)
The prefrontal cortex （PFC） critical for higher cognition is implicated in neuropsychiatric diseases, such as Alzheimer＇s disease, depression and schizophrenia. The voltage-activated Kv7/KCNQ/M-channel or M-current modulates the neuronal excitability that defines the fundamental mechanism of brain function. However, whether M-current functions to regulate the excitability of PFC neurons remains elusive. In this study, we recorded the native M-current from PFC layer V pyramidal neurons in rat brain slices and showed that it modulated the intrinsic excitability and synaptic responses of PFC pyramidal neurons. Application of a specific M-channel blocker XE991 （40 pmol/L） or opener retigabine （10 pmol/L） resulted in inhibition or activation of M-current, respectively. In the currentclamp recordings, inhibition of M-current was evidenced by the increased average spike frequency and the reduced first inter-spike intervat （ISI）, spike onset latency and fast afterhyperpolarization （fAHP）, whereas activation of M-current caused opposite responses. Furthermore, inhibition of M-current significantly increased the amplitude of excitatory postsynaptic potentials （EPSPs） and depolarized the resting membrane potential （RMP） without affecting the miniature EPSC （mEPSC） frequency. These data demonstrate that voltage-gated neuronal Kv7/KCNQ/M-current modulates the excitability and synaptic transmission of PFC neurons, suggesting that pharmacological modulation of M-current in the PFC may exert beneficial effects on cognitive deficits implicated in the pathophysiology of neuropsychiatric disorders.